ASPEK-ASPEK HUKUM PERKREDITAN PADA BANK EKA AYU ARTHA BHUWANA KABUPATEN GIANYAR - Sakih Sastrawan, I Gede; Putra Atmadja, Ida Bagus (Kertha Semaya : Journal Ilmu Hukum, 2013)
By knowledge of law that owned by bank staff hence it will assist them to easy to carry out their duty and avoid a mistake which damage the bank in transaction that conducted. As for the form of credit security which have been conducted by the Bank Eka Ayu Artha Bhuwana Gianyar as follows: through restructurisation and form of credit security through law institution.
Keywords: Staff Human Resources, Restructurisation, Law Institution